Technology Implementation Impacting the Outcomes of Patients with CAP - Vines, Caroline; Dean, Nathan C. (Seminars in Respiratory and Critical Care Medicine, 2012)
Community-acquired pneumonia (CAP) combined with influenza is the eighth leading cause of death in the United States. This article examines the literature to understand and describe whether technology implementation has impacted the outcomes of patients with CAP. We conducted an electronic search of PubMed and scanned references of articles meeting inclusion criteria. Twenty-six articles were included in this review. We surveyed this literature for answers to the following questions: Can technology be used to improve quality of care and guideline compliance in CAP? How can we overcome the behavioral bottleneck that prevents adoption of computerized decision support systems? How reliable are our data in the era of electronic medical records? What are the risks associated with technology implementation? No articles demonstrated that technology implementation improves outcomes in the care of patients with CAP.
Keywords: pneumonia; technology; computerized decision support; electronic medical records